Standard and Low Molecular Weight Heparin Have no Effect on Tissue Plasminogen Activator Induced Plasma Clot Lysis or Fibrinogenolysis - Weitz, Jeffrey I; Kuint, Jacob; Leslie, Beverly; Hirsh, Jack (Thrombosis and Haemostasis, 1991)
Although heparin is often given as an adjunct to tissue plasminogen activator (t-PA), the effect of heparin on t-PA induced fibrin(ogen)olysis is controversial. To address this controversy, we examined the effects of standard and low molecular weight heparin (enoxaparine) on both t-PA induced clot lysis and t-PA mediated fibrinogenolysis in a human plasma system. Accordingly, 125I-labeled fibrin clots were incubated in t-PA containing citrated plasma in the presence or absence of these glycosaminoglycans, and the extent of thrombolysis was determined by measuring residual radioactivity of the clots, while Bβ1–42 levels were used as a specific index of fibrinogenolysis. Over a wide range of t-PA concentrations (0.1 to 1.6 μg/ml), neither heparin nor enoxaparine influences either t-PA induced clot lysis or t-PA mediated Bβ1–42 generation. These findings suggest that either agent could be used as an adjunct to t-PA without compromising either the thrombolytic potential of t-PA or its clotselectivity